REDD1 functions at the crossroads between the therapeutic and adverse effects of topical glucocorticoids. Issue 1 (11th December 2014) - Baida, Gleb; Bhalla, Pankaj; Kirsanov, Kirill; Lesovaya, Ekaterina; Yakubovskaya, Marianna; Yuen, Kit; Guo, Shuchi; Lavker, Robert M; Readhead, Ben; Dudley, Joel T; Budunova, Irina
Abstract Cutaneous atrophy is the major adverse effect of topical glucocorticoids; however, its molecular mechanisms are poorly understood. Here, we identify stress‐inducible mTOR inhibitor REDD1 (regulated in development and DNA damage response 1) as a major molecular target of glucocorticoids, which mediates cutaneous atrophy. In REDD1 knockout (KO) mice, all skin compartments (epidermis, dermis, subcutaneous fat), epidermal stem, and progenitor cells were protected from atrophic effects of glucocorticoids. Moreover, REDD1 knockdown resulted in similar consequences in organotypic raft cultures of primary human keratinocytes. Expression profiling revealed that gene activation by glucocorticoids was strongly altered in REDD1 KO epidermis. In contrast, the down‐regulation of genes involved in anti‐inflammatory glucocorticoid response was strikingly similar in wild‐type and REDD1 KO mice. Integrative bioinformatics analysis of our and published gene array data revealed similar changes of gene expression in epidermis and in muscle undergoing glucocorticoid‐dependent and glucocorticoid‐independent atrophy. Importantly, the lack of REDD1 did not diminish the anti‐inflammatory effects of glucocorticoids in preclinical model. Our findings suggest that combining steroids with REDD1 inhibitors may yield a novel, safer glucocorticoid‐based therapies.